Le Transport Maritime à Courte Distance du Plateau des Guyanes à la Mer des Caraïbes : la perception des parties prenantes - Sherline Dumano; Rémy Louis Budoc; Claude Fiore (Territoire en Mouvement)
The purpose of this research is to analyse how a Short Sea Shipping (SSS) service would be perceived by stakeholders if it were implemented within their geographical area comprised of the Guiana Shield and Caribbean Sea. Given the background of unbalanced external trade among the territories examined by this work, the development of infrastructures and rational modes of transport is necessary to liberate and encourage intra-regional exchange. In French Guiana, the trade imbalance is underpinned by its high reliance on imports principally from mainland France and Europe, despite it sharing a border with Brazil – Macapá, the capital of the Brazilian state of Amapá, is only 700 km away. This continental proximity allows illegal or informal economic activity to thrive, especially since there is very little infrastructure to facilitate organised, structured trade. With intra-regional shipping services being largely non-existent at the moment, the scientific goal of this work is to correlate the vision and perception of those parties most involved in this sector for the purposes of determining whether a projected SSS service could be a credible transport option and identifying the conditions required to ensure the feasibility of its implementation and prosperity.